POM QM for Windows Training for Industrial Engineering Students at the University of Serang Raya (UNSERA) in Solving Linear Programming Problems in Everyday Life and the World of Work - I Gede Marendra; I Made Aryata; Irmawan Afgani (PT FORMOSA CENDEKIA GLOBAL, 2023)
POM QM for Windows training on the Linear program is carried out with the aim of solving the problem of allocating resources which is quite complex in the best and easiest way to do it. This training was conducted for students by explaining the use of the POM QM application for Windows and ending with a simulation by students. The output of this training is that students already understand how to install and use the POM QM application in solving linear programming problems and students are quickly able to draw conclusions about linear programming problems based on the results of application calculations. As well as with the POM QM for Windows training, participants or industrial engineering students are able to solve complex linear programming problems quickly and precisely.